ANALISIS PENGARUH MULTIVARIABEL TERHADAP KEANDALAN SARANA BANTU NAVIGASI PELAYARAN (SBNP) DI PELABUHAN UTAMA MAKASSAR - Rustam Rustam; Muhammad Jamal; Danial Danial (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2021)
This study aims to determine the effect of human resources, technology, ATONs adequacy, ATONs maintenance, ATONs replacement, and ATONs security partially and simultaneously on the reliability of ATONs at Makassar Main Port. This research was conducted from February 2019 to April 2019 at the Makassar Class I Navigation District Office with the respondent sampling technique using a simple random sampling technique, taking samples from the total number of Civil Servants at the Makassar Class I Navigation District Office as respondents to determine the effect of independent variables on the dependent variable either partially or simultaneously. Data processing in this study used the SPSS for Windows Version 20 program. The results of this study indicate that, (1) Human resources, technology, ATONs adequacy, ATONs maintenance, ATONs replacement, and ATONs security partially have a positive and significant effect on the reliability of ATONs in Makassar Main Port. (2) Human resources, technology, ATONs adequacy, ATONs maintenance, ATONs replacement, and ATONs security simultaneously have a positive and significant effect on the reliability of ATONs at Makassar Main Port.